Combination Therapy Is Not Associated with Decreased Mortality in Infectious Endocarditis: A Systematic Review and Meta-Analysis - Parisa Farahani; Felicia Ruffin; Mohammad Taherahmadi; Maren Webster; Rachel E. Korn; Sarah Cantrell; Lana Wahid; Vance G. Fowler; Joshua T. Thaden (Microorganisms)
Untreated infective endocarditis (IE) is uniformly fatal. The practice of combination antibiotic therapy for IE is recommended by treatment guidelines but largely unsupported by high-quality evidence. This study aimed to assess the efficacy of combination antibiotic therapy compared to monotherapy in IE through a systematic review and meta-analysis. We systematically searched MEDLINE, Embase, Cochrane, Web of Science, and CINAHL from inception to 29 July 2024. Studies reporting mortality outcomes of combination therapy versus monotherapy in adult patients with IE were included. Non-English papers and studies with less than 10 patients in the combination therapy group were excluded. Two reviewers independently assessed the studies and extracted relevant data. Summaries of odds ratios (ORs) with 95% confidence intervals (CIs) were evaluated using random-effects models. Out of 4545 studies identified, 32 studies (involving 2761 patients) met the inclusion criteria for the meta-analysis. There was no significant difference in the risk of all-cause mortality between the monotherapy and combination therapy groups (OR = 0.90; 95% CI = 0.67–1.20). Similar results were observed in subgroup analyses based on mortality time points, bacterial species, publication date, and type of study. Studies conducted in Europe reported a statistically significant decrease in overall mortality risk with combination therapy (OR = 0.67; 95% CI = 0.51–0.89), though this result was driven entirely by a single outlier study. Combination antibiotic therapy in patients with IE was not associated with reduced mortality.